^{38}K isomer production via fast fragmentation - K. A. Chipps; R. L. Kozub; C. Sumithrarachchi; T. Ginter; T. Baumann; K. Lund; A. Lapierre; A. Villari; F. Montes; S. Jin; K. Schmidt; S. Ayoub; et al. (Physical Review Accelerators and Beams, 2018)
In radioactive ion beam experiments, beams containing isomers can be of interest in probing nuclear structure and informing astrophysical reaction rates. While the production of mixed in-flight ground state and isomer beams using nucleon transfer can be generally understood through distorted wave Born approximation methodology, low-spin isomer production via fast fragmentation is relatively unstudied. To attain a practical understanding of low-spin isomer production using fast fragmentation beams, a test case of ^{38}K/^{38m}K was studied at the National Superconducting Cyclotron Laboratory’s ReAccelerated Beam facility. Starting from lise++ predictions, the fragmentation momentum distribution was sampled to determine isomer production. In addition, the effects of the gas stopper gradient and charge breeding times were examined. In the case of ^{38}K, isomer production peaks at ∼57%. This maximum is observed just off the lise++ predicted optimum magnetic rigidity, with only small losses in beam intensity within a few percent of this optimum rigidity setting. Control of the isomer fraction was also achieved through the modification of charge breeding times. Fast fragmentation appears to be a feasible method for production of low-spin isomeric beams, but additional study is necessary to better describe the mechanism involved.